A Flexible Hazard Rate Model for Grouped Duration Data - Wolfgang Hess (Lund University, School of Economics and Management, Department of Economics, 2009)
This paper proposes a discrete-time hazard regression approach based on the interrelation between hazard rate models and excess over threshold models, which are frequently encountered in extreme value modelling. The proposed duration model incorporates a grouped-duration analogue of the well-known Cox proportional hazards model and a proportional odds model as special cases. The theoretical setup of the model is motivated, and simulation results are reported to suggest that it performs well. A numerical example using US unemployment data is also provided.
Keywords: C41; J64; 330; Discrete-Time Duration Model; Hazard Rate; Threshold Excess Model; Unemployment Duration